-13=f-4+-15

Simple and best practice solution for -13=f-4+-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13=f-4+-15 equation:



-13=f-4+-15
We move all terms to the left:
-13-(f-4+-15)=0
We add all the numbers together, and all the variables
-(f-19)-13=0
We get rid of parentheses
-f+19-13=0
We add all the numbers together, and all the variables
-1f+6=0
We move all terms containing f to the left, all other terms to the right
-f=-6
f=-6/-1
f=+6

See similar equations:

| x(x−2)=8 | | 8r-8=2r+10 | | 14g-98+3g9=7 | | 2x+9=-2x-11 | | 5(x-3)+22=100 | | -3=c/5–4 | | V^2-20v-44=0 | | K+6=-6-8k+5k | | 2+k+4K-7=3k+1 | | 0=-7p+7+8p | | 8(x-3)-6x=15 | | 23=7x-4-8 | | -12=-7x+4x | | -2=1+3x-4x | | 4d-4=9 | | -6+3b-7b=6 | | (4+3b)+(5+3b)= | | r-16=-14 | | w-18=11 | | 4(5-3x)-5(3x+2)=8-6x | | a+19=-15 | | a+17=-20 | | 10x-23+106=180 | | 2x+34=2 | | 5n-1=49 | | 4(4+v)+39v=10v | | 2x-18=66 | | 3/4y+6=-12 | | 4x+3=−9 | | 36+26+3x+1=180 | | -3k^2+4k-8=0 | | -x+34=4(x-5)-1 |

Equations solver categories